PRIDE AND PREJUDICE BEYOND THE GLASS CEILING : BRAZILIAN FEMALE EXECUTIVE ’ S PSYCHOLOGICAL TYPE - Antonio Carvalho Neto (Revista de Ciências da Administração, 2014)
This paper intends to relate characteristics of female executive psychological type with their male colleagues in corporations operating in Brazil (CEOs, VPs/directors and top managers). The theoretical framework explores the glass ceiling and the prejudices faced by female executives. It was developed a mixed qualitative- quantitative method. In the quantitative part we interviewed 743 men and 222 women from 344 corporations. We applied also the questionnaire MBTI to 430 of these executives. In the qualitative part we held focus groups with 227 individuals and 104 semi- structured interviews. The most active psychological MBTI type found was the ESTJ, both to men and women. The dominant characteristics in this type is more rational, logical and less emotional. Prejudices are huge: women need to work harder to show that they are as competent as men. They also live the society’s pressure in relation to the roles as mother and wife.